Answer :

Given that y = 1 is a root of the equation ay2 + ay + 3 = 0

a.12 + a.1 + 3 = 0


a + a + 3 = 0


2a + 3 = 0


a = - 3/2


Also y = 1 is a root of the equation y2 + y + b = 0


12 + 1 + b = 0


2 + b = 0


b = - 2



Thus the value of ab = 3


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses